Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/mec.16155
|View full text |Cite
|
Sign up to set email alerts
|

Within‐individual repeatability in telomere length: A meta‐analysis in nonmammalian vertebrates

Abstract: Telomeres are highly conserved repetitive sequences of non-coding DNA that cap the ends of linear chromosomes of eukaryotic species and contribute to genomic integrity maintenance (Blackburn, 1991).Telomeres shorten with every cell division due to the end replication problem (inability of DNA polymerase to copy terminal DNA) (Levy et al., 1992). Additionally, telomere shortening can be accentuated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 203 publications
(152 reference statements)
8
42
0
Order By: Relevance
“…Figure 3e), although the estimate for TRF was significantly more negative than for qPCR (QM 2 11.20, p = .004). Similar methodological differences have been reported previously (e.g., see Kärkkäinen et al, 2021;Wilbourn et al, 2018). We cannot disregard the differences between methods in the small number of studies and effect sizes using the TRF technique (n = 4 studies, k = 24), and more studies are needed to elucidate the observed pattern.…”
Section: Ta B L E 1 (Continued)supporting
confidence: 66%
See 1 more Smart Citation
“…Figure 3e), although the estimate for TRF was significantly more negative than for qPCR (QM 2 11.20, p = .004). Similar methodological differences have been reported previously (e.g., see Kärkkäinen et al, 2021;Wilbourn et al, 2018). We cannot disregard the differences between methods in the small number of studies and effect sizes using the TRF technique (n = 4 studies, k = 24), and more studies are needed to elucidate the observed pattern.…”
Section: Ta B L E 1 (Continued)supporting
confidence: 66%
“…In addition, their biological implications at the organismal level remain unclear. Other biological characteristics, such as the change with age or the withinindividual repeatability, have also been shown to be sensitive to the method employed in telomere estimation (Atema et al, 2019;Kärkkäinen et al, 2021;Remot et al, 2021). Therefore, these technical limitations could influence any inferences about past stress exposure or future long-term consequences for a given telomere length if not considered beforehand.…”
Section: Further Considerationsmentioning
confidence: 99%
“…Second, qPCR plates contained both 0.5 and 3 months samples, and between-plate variance was negligible in all our models, highlighting that this element of our methodology had little impact on our results. Overall, we monitored procedural efficiency throughout data collection and did not identify any other potential methodological sources of variation; the repeatability estimates for the T/S ratios estimated from within-individual samples were well within the range of those for similar species in other qPCR studies ( Kärkkäinen et al, 2021 ). Consequently, we believe that the increase in telomere length observed in our study has a biological explanation.…”
Section: Discussionmentioning
confidence: 84%
“…The other eight studies used the quantitative polymerase chain reaction (qPCR, n = 7), which relies on the quantification of the highly conserved (TTAGGG) n sequence for a Southern blot variation (TeloTAGGG for telomere quantification (n = 1) [69]. TRF-based studies are highly repeatable within individuals, whereas qPCR based studies are less repeatable and more variable than TRF because they are more prone to measurement errors [70]. qPCR can also bias measurements of telomere length because some species that exhibit interstitial telomeric repeats will artificially enlarge telomere length [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, telomerase exhibits higher activity in developing organisms as compared to adults [77]. Ectotherms such as amphibians and reptiles have telomerase that is active throughout adulthood while endotherms reduce telomerase expression almost to non-detectable levels as they reach maturity [11,70]. However, there is conflicting evidence on these observations, as telomerase activity has been detected in adult common terns and European Storm Petrels among other species [78,79].…”
Section: Discussionmentioning
confidence: 99%